2019
DOI: 10.1016/j.smrv.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and sleep problems: A systematic review and meta-analysis

Abstract: The pathological use of the internet-conceptualized as 'internet addiction'-might be crucial in initiating and increasing sleep disturbances in the community. While inconsistent evidence is reported regarding the association of internet addiction and sleep disturbances, the severity of this association remains unclear. This systematic review and meta-analysis were conducted to increase our understanding of the relationship between internet addiction and sleep disturbances. A systematic review was conducted thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
222
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 311 publications
(238 citation statements)
references
References 63 publications
8
222
2
6
Order By: Relevance
“…Delayed bedtimes and late waking times may further lead to the rhythm desynchronization and impact school performance [15]. Other potential mechanisms in disrupting sleep may include psychological stimulation (i.e., excited mood due to use of social media) [16], light-emitting screens (i.e., light may suppress sleep-promoting hormones like melatonin that are typically elevated before bedtime) [17], and shortened sleep duration [18]. Similar considerations exist for online gaming.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed bedtimes and late waking times may further lead to the rhythm desynchronization and impact school performance [15]. Other potential mechanisms in disrupting sleep may include psychological stimulation (i.e., excited mood due to use of social media) [16], light-emitting screens (i.e., light may suppress sleep-promoting hormones like melatonin that are typically elevated before bedtime) [17], and shortened sleep duration [18]. Similar considerations exist for online gaming.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to investigate the relationship between sleep and IA. Some studies have reported an association between IA and depression and sleep disturbance [22,23], nighttime sleep duration and subjective insomnia [24], poor sleeping habits [25], smartphone dependence [26], and sleep quality [27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported bidirectional associations between insomnia symptoms and depression/anxiety (Jansson-Fröjmark and Lindblom 2008;Luo et al 2013). Sleep problems are a significant health concern among adolescents, and it has been associated with technology use (Cheung and Wong 2011;Sami et al 2018;Zhang et al 2017; see Alimoradi et al (2019) for a recent systematic review and meta-analysis). Poor sleep quality prevalence rates have been reported in various studies.…”
mentioning
confidence: 99%